Kekosongan Hukum Pengaturan Transportasi Online Berdasarkan Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu-Lintas Angkutan Jalan - Saham Lamganda; Umar Aris; Resi Pranacitra (Jurnal Multidisiplin Dehasen (MUDE), 2023)
One of the efforts that can be made to reduce traffic congestion in Jakarta is by maximizing the public transportation system, including both mass transportation and individual transportation. The land transportation modes in Jakarta consist of City Buses, City Transport (angkot), Electric Railways (KRL), and Mass Rapid Transit (MRT).In this digital era, there has been the emergence of individual public transportation, where individuals with private vehicles can act as public transport providers through a private company's application platform as the booking medium. Therefore, it is very interesting to examine the issues of public transportation using private vehicles in Jakarta through normative juridical research, which is a study based on literature review using primary materials such as laws and regulations, references, and legal documents related to the issue. In this case, the implementation of Law No. 22 of 2009 concerning Road Traffic is applicable. Through this scholarly journal, the author aims to elaborate on the legal gaps in the world of transportation using online applications for booking, commonly known as Online Transportation.